Pengembangan Sistem Informasi Pemesanan Paket Wisata (Studi Kasus : Agen Wisata Liburan Sekolah) - Rodiah Rodiah; Buce Trias Hanggara; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Liburan sekolah is a travel agency engaged in services, which offer tour packages and guide tourists in visiting the Thousand Islands tours. To make a tour package booking, visitors must contact customer service via telephone or whatsApp and customer service records each order entered manually. This becomes less effective because customer service must reply to every order that comes in and checks every transaction made by a visitor. Based on this we need an information system that can facilitate visitors and customer service in the process of ordering and registering orders. In the process of developing a system used a method that is carried out sequentially or commonly known as the waterfall method. The results of the needs analysis yielded 15 functional needs which were described in the use of case diagrams and the results of system design were described in sequence diagrams, activity diagrams and database modeling. In the process of implementing the system, the Laravel and mysql framework are used for database storage, at this stage 6 controllers are generated. Based on the results of black box testing shows all functions can run well and is declared valid and based on the results of the User Acceptance Testing (UAT) test with 10 respondents producing an index value of 89.6% can conclude the system can be accepted. Based on the results of this study produced a tour package booking information system that can facilitate tourists and admins and the transaction process